Intentionality and meditation of information in the context of digital informational enviroments - Sanchez, Fernanda Alves [UNESP]; Vidotti, Silvana Aparecida Borsetti Gregorio; Vechiato, Fernando Luiz; Almeida Junior, Oswaldo Francisco de [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2022)
The concept of Intencionality essentially encompasses the sociocognitive background of informational subjects who under the influence of different contexts (political, social, economic, technological) produce, interpret, mediate, use, and appropriate information based on their behaviors, skills, abilities, and experiences. Within the post-custodial paradigm, technological development provides an increase in the information that is generated, especially in digital informational environments. Thus, studies that can enhance the way these environments are designed are necessary so that they provide quality in findability, access, use, and appropriation of information. This research seeks to point out the relationships between the concepts of Intentionality and Information Mediation in the context of the studies responsible for building projects for digital informational environments -Information Architecture and Findability. In this sense, it was possible to develop theoretical reflections by correlating the terms and foundations of the concepts of Intentionality and Information Mediation. In addition to relevant discussions pertinent to the field of Information Science in the face of a more practical approach in the context of the digital informational environment.
Keywords: Intencionality; Mediation of Information; Information Architecture; Information Findability; Information and Technology